Obtenção de micro e nanocelulose para preparação de membranas poliméricas como barreira seletiva - Favero, Diana (My University, 2015)
The use of polymeric membranes has been extensively studied for separation processes. The study of materials and methodologies for development of such membranes for cost reduction and improvement in their properties are necessary to face this scenario. In the preparation of membranes, organic materials such as polymers and elastomers are employed with the possibility of incorporation of reinforcement materials and to modify the characteristics to favor certain processes. These membranes are called composite, they are obtained by dispersing a physical component in the polymer matrix, where the size of the dispersed phase varies from micrometer to nanometer scale and the interface between the phases must be well defined. Natural fibers has highlighted as a reinforcing material due to their renewable nature and vast source of raw materials, in addition having good mechanical properties and low cost. The plant cell wall cellulose can be purified, isolated and incorporated into membranes acting as reinforcing agent. The hydrolysis techniques are employed methodologies for isolating crystals of cellulose, using different acids resulting in different properties. In this work we used Kraft pulp from Eucalyptus ssp following two methods for isolation (acids HCl and H2SO4) of micro (MCC) and nanocrystals (NCC) of cellulose. Incorporating these materials into membranes of polysulfone (PSf) were evaluated for permeate flux, rejection protein, contact angle and scanning and transmission electron microscopy. Nanocelulose presented diameter and length defined and favorable aspect ratio for incorporation into polymeric membranes. The solution obtained after hydrolysis with H2SO4 can be consider more stable as it presented less agglomerations. The addition of microcellulose and cellulose nanocrystals to membranes proved satisfactory for the preparation of polymeric membranes. There was an increase in rejection of the proteins, selectivity and hydrophilicity for the reinforced membranes, especially with nanocelulose obtained by hydrolysis with H2SO4.
O uso de membranas poliméricas vem sendo extensivamente estudado para operações de separação. O estudo de materiais e metodologias para desenvolvimento de tais membranas para redução de custos e melhora em propriedades, faz-se necessário frente a este cenário. No processo de preparação de membranas, materiais orgânicos, tais como polímeros, elastômeros, são empregados com a possibilidade de incorporação de materiais de reforço e para modificar as características de forma a favorecer determinados processos. Estas membranas são chamadas compósitas, obtidas pela dispersão física de um componente na matriz polimérica, sendo que as dimensões da fase dispersa variam da escala micrométrica a nanométrica e a interface entre as fases deve ser bem definida. As fibras naturais tem destaque como materiais de reforço, devido sua natureza renovável e sua vasta fonte de matéria-prima, além de apresentarem boas propriedades mecânicas e baixo custo. A celulose presente na parede celular de plantas pode ser purificada, isolada e incorporada a membranas atuando como agente de reforço. As técnicas de hidrólise são metodologias empregadas para isolar cristais de celulose, que utilizam diferentes ácidos, resultando em diferentes materiais. Neste trabalho foi empregada celulose 1kraft de Eucalyptus ssp seguindo duas metodologias para isolamento de micro (MCC) e nanocristais celulósicos (CNC) utilizando ácido clorídrico e ácido sulfúrico (HCl e H2SO4). A incorporação destes materiais em membranas de polissulfona (PSf) foi avaliada por fluxo de permeado, rejeição de proteínas, ângulo de contato e microscopia eletrônica de varredura e de transmissão. As nanoceluloses apresentaram diâmetro, comprimento definidos e razão de aspecto favorável a incorporação em membranas poliméricas. A solução de nanocelulose obtida pela hidrólise com H2SO4 pode ser considerada mais estável, pois apresentou menos aglomerações. A adição de microcelulose e nanocristais de celulose às membranas de polisulfona (PSf) se mostrou satisfatória para a preparação das membranas poliméricas. Ocorreu aumento na rejeição das proteínas submetidas, da seletividade e da hidrofilia para as membranas reforçadas, principalmente com nanocelulose obtida por hidrólise com HCl.
Keywords: Filtração por membranas; Hidrólise; Ácido sulfúrico; Ácido clorídrico; Celulose; Membrane separation; Hydrolysis; Sulphuric acid; Hydrochloric acid; Cellulose